Paracervical block before laparoscopic total hysterectomy: a randomized controlled trial - Güngördük, Kemal; Gülseren, Varol; Taştan, Leyla; Özdemir, İsa Aykut (My University, 2024)
Objective: To test the hypothesis that paracervical block with 0.5 % bupivacaine decreases postoperative pain after total laparoscopic hysterectomy (TLH). Materials and method: This randomized double-blind placebo control trial included 152 women. We injected 10 mL 0.5 % bupivacaine (study group, n = 75) or 10 mL normal saline (control group, n = 77) at the 3 and 9 o'clock positions of the uterine cervix. The primary outcome was the visual analog scale score (VAS) determined 1 h (h) postoperatively. Results: The 152 patients did not differ in their baseline demographics or perioperative characteristics. The mean VAS 1 h postoperatively was significantly lower in the study group than in controls (5.7 ± 1.2 vs. 6.8 ± 1.1, P < 0.001). The average VAS at 30 min, 3 h, and 6 h postoperatively was also significantly lower in the study group. Patients in the study group had a significantly lower analgesic requirement than did controls during the first 24 h postoperatively (6 [7.8 %] vs. 16 [21 %], P = 0.021). Total QoR-40 questionnaire scores were higher in patients who received bupivacaine. Conclusion: Paracervical bloc with 0.5 % bupivacaine just before TLH is an effective and safe method to reduce pain and lower postoperative analgesic requirement. URL link that leads directly to the trial registration: https://clinicaltrials.gov/ct2/show/NCT05341869?cond=NCT05341869&draw=2&rank=1.
Keywords: Laparoscopic Hysterectomy; Paracervical Block; Randomized Trial